Fusarium ear rot and how to screen for resistance in open pollinated maize in the Andean regions - Silva, E.; Mora, E.A.; Medina Hoyos, Alicia Elizabeth; Vasquez, J.; Valdez, D.; Danial, D. L.; Parlevliet, J. E. (Springer Nature, 2025)
Ears infected with ear rot were collected from five provinces in Ecuador. Of the 44 samples analysed 26 carried Fusarium verticillioides, 11 F. subglutinans, two F. graminearum and five carried fungi different from Fusarium. The pathogenicity of ten isolates, seven of F. verticillioides and three of F. subglutinans, were tested. Per isolate 30 ears of the susceptible cultivar Mishca were inoculated by pricking a steel pin, dipped into a spore suspension, through the husks in the central part of the ear 14 days after mid-silk. Ears inoculated with sterile water and ears without any treatment, natural infection, served as controls. The disease severity (DS) of the ears ranged from 14 to 58% ear rot, the range being similar for both species. The DS of the water control, 19%, was much higher than that of the natural control of 2%. Five strains gave a DS of over 40%, significantly higher than the water control. The DS of the others were similar to the water control. In a series of experiments the effect of various methods of applying Fusarium spores through the husks into young ears were compared. All tested methods resulted in DSs significantly higher than those of the two controls. Inoculation with tooth picks and steel pins dipped in a spore suspension gave similar ear rot percentages. Inoculations at 7 to 14 days after mid-silk produced the highest DS’s. There was no significant effect of spore concentration on the DS. Cultivars differed considerably, the range being from around 20% to over 50%. Surprisingly, only wounding the husks, the sterile water control, resulted in a fairly high DS, much higher than that of the natural control. As the ranking order of the cultivars after wounding only and after inoculation did not seem to be different from the ranking order of the natural control it is suggested to use in areas with high inoculum pressures like the Andes only wounding by means of a steel pin for screening for resistance to maize ear rot.